System Identification for a Model-Based Observer of a Road Roughness Profiler - McCann, R.; Nguyen, S. (2007 IEEE Region 5 Technical Conference, 2007)
The increasing numbers of paved roadways throughout the world have motivated the development of automated methods of assessing road pavement conditions. A method of developing an automated profiling vehicle that can rapidly acquire and accurately determine road roughness levels is presented. It is shown that it is important to compensate for the chassis dynamics in order to minimize the effects of suspension system interactions when computing the road roughness level. Experimental results from a prototype vehicle are detailed where the effectiveness of the vehicle design method is demonstrated.